The Crime of 1873 - Friedman, Milton (Journal of Political Economy, 1990)
The U.S. Coinage Act of 1873 eliminated provision for the free coinage of silver. That act cast the die for a gold standard. The conventional view is that "the act of 1873 was a piece of good fortune." This paper indicates that it was the opposite–a mistake that had highly adverse consequences. This is a judgment about 1873, not 1896. By 1896, when William Jennings Bryan ran for president on a "free-silver ticket," it was too late to undo the damage. Bryan was trying to close the barn door after the horse had been stolen.